A murine model of Lyme disease demonstrates that Borrelia burgdorferi colonizes the dura mater and induces inflammation in the central nervous system. - Timothy Casselli; Ali Divan; Emilie E Vomhof-DeKrey; Yvonne Tourand; Heidi L Pecoraro; Catherine A Brissette (PLoS Pathogens, 2021)
Lyme disease, which is caused by infection with Borrelia burgdorferi and related species, can lead to inflammatory pathologies affecting the joints, heart, and nervous systems including the central nervous system (CNS). Inbred laboratory mice have been used to define the kinetics of B. burgdorferi infection and host immune responses in joints and heart, however similar studies are lacking in the CNS of these animals. A tractable animal model for investigating host-Borrelia interactions in the CNS is key to understanding the mechanisms of CNS pathogenesis. Therefore, we characterized the kinetics of B. burgdorferi colonization and associated immune responses in the CNS of mice during early and subacute infection. Using fluorescence-immunohistochemistry, intravital microscopy, bacterial culture, and quantitative PCR, we found B. burgdorferi routinely colonized the dura mater of C3H mice, with peak spirochete burden at day 7 post-infection. Dura mater colonization was observed for several Lyme disease agents including B. burgdorferi, B. garinii, and B. mayonii. RNA-sequencing and quantitative RT-PCR showed that B. burgdorferi infection was associated with increased expression of inflammatory cytokines and a robust interferon (IFN) response in the dura mater. Histopathologic changes including leukocytic infiltrates and vascular changes were also observed in the meninges of infected animals. In contrast to the meninges, we did not detect B. burgdorferi, infiltrating leukocytes, or large-scale changes in cytokine profiles in the cerebral cortex or hippocampus during infection; however, both brain regions demonstrated similar changes in expression of IFN-stimulated genes as observed in peripheral tissues and meninges. Taken together, B. burgdorferi is capable of colonizing the meninges in laboratory mice, and induces localized inflammation similar to peripheral tissues. A sterile IFN response in the absence of B. burgdorferi or inflammatory cytokines is unique to the brain parenchyma, and provides insight into the potential mechanisms of CNS pathology associated with this important pathogen.